(untitled) (American Journal of Islam and Society, 2014)
On November 8, 2013, Syed Muhd Khairudin Aljunied (National University of Singapore; Fulbright Fellow, Columbia University) addressed the topic of “Muslim Cosmopolitanism.” The event was held at the IIIT headquarters in Herndon, Virginia. He began his talk with a personal example: He is the child of an Arab father and an Indian mother, his culture is Malay, he prefers to talk in either Malay or English, and he understands Chinese. Thus, he is a living example of his assertion that “being Muslim is part and parcel of being able to appreciate many cultures … We are all hybrids,” and therefore it is only natural for Muslims to embrace diversity. While this was true for the first millennium of Islamic civilization, it is, unfortunately, “not the case today.” Aljunied cited several examples of how contemporary Muslims have put this reality aside. For example, he raised the question of why, when a Muslim engages in something that is clearly wrong, do Muslims apologize by saying that he/she is a “bad Muslim,” instead of a “bad person,” or become offensive by saying that the action was somehow justified. He noted that this is “an unhealthy development in the world in general, and especially in the United States” – one that Muslims should abandon. Instead, Muslims need to study their history and understand exactly who they are. With this goal in mind, he praised AbdulHamid AbuSulayman’s Crisis in the Muslim Mind (IIIT: 1993) for its analysis of such concerns ...